Do aliens speak physics? : and other questions about science and the nature of reality - Whiteson, Daniel (W. W. Norton & Company, 2025)
"When the long-awaited day dawns and the aliens finally arrive on Earth, they might eat us and destroy the planet -- or, just maybe, they might share the secrets of the Universe with us. When that time comes, will we be able to cross the communication barrier to beg for our lives? If the aliens do hold out those precious jewels of knowledge, will we even be able to grasp them? It's long been assumed, in both science fiction and real scientific efforts to communicate with hypothetical aliens, that math and physics could serve as a universal language connecting us with extraterrestrial minds. But as humanity draws ever closer to the possibility of an interplanetary future and expands its agelong search for alien life and intelligence, beloved author and physicist Daniel Whiteson and best-selling cartoonist Andy Warner wonder if we should be so sure. In Do Aliens Speak Physics?, they take readers on a wild adventure to the edges of space-time, science, and the imagination to investigate whether an alien-human mind meld could ever be achieved. Deploying cutting-edge physics, deep philosophical insight, and plenty of cartoons, Whiteson and Warner explode what we thought we knew about talking to our cosmic neighbors -- and even science itself -- by asking and answering questions both lighthearted and profound. Would aliens even need science to build the technology that brings them to Earth? Is it possible that they could experience the Universe very differently from us -- tasting electrons and smelling photons? Would the extraterrestrials have to perceive "electrons" and "photons" at all, or are these particles only convenient concepts for our human minds? At bottom, does physics reveal fundamental truths about the Universe, as we so often believe, or might it in fact tell us more about ourselves?" --